Two-dimensional tracking and TDI are consistent methods for evaluating myocardial longitudinal peak strain in left and right ventricle basal segments in athletes - Cappelli Brunello; Moretti Andrea; Vono Maria; Di Tante Valentina; Manetti Paolo; Gianassi Marco; Toncelli Loira; Stefani Laura; Pedrizzetti Gianni; Galanti Giorgio (Cardiovascular Ultrasound, 2007)
Abstract Background Myocardial contractility can be investigated using longitudinal peak strain. It can be calculated using the Doppler-derived TDI method and the non-Doppler method based on tissue tracking on B-mode images. Both are validated and show good reproducibility, but no comparative analysis of their results has yet been conducted. This study analyzes the results obtained from the basal segments of the ventricular chambers in a group of athletes. Methods 30 regularly-trained athletes were submitted to an echocardiography at rest and after handgrip. Starting from the four-chamber view, overall myocardial function and regional velocities were evaluated. The images obtained were processed to determine strain in left and right ventricle basal segments. Strain was calculated using the TDI method and a validated "speckle tracking" or, more correctly, "feature tracking" algorithm. The statistical analysis included a Student's t-test (p < 0.05). Results The range of strain values obtained is in agreement with the data reported in the literature. In the left ventricle (LV) the average strain values of the basal segments calculated with TDI on IVS and LW at rest and after stress were: -21.05 ± 3.31; -20.41 ± 2.99 and -20.05 ± 2.61; -21.20 ± 2.37, respectively. In the right ventricle (RV) the same method gave IVS and LW strain values at rest of -22.22 ± 2.58 ; -24.42 ± 5.84, and after HG of -22.02 ± 5.20 ;-23.93 ± 6.34. The values obtained using feature tracking were: LV at rest -20.48 ± 2.65 for IVS, and -21.25 ± 2.85 for LW; LV after HG: -19.48 ± 3 for IVS and -21.69 ± 3.85 for LW. In RV at rest: -21.46 ± 3.25 for IVS and -24.13 ± 5.86 for LW; RV after HG: -24.79 ± 7.9 for IVS and -24.13 ± 7.0 for LW. Tissue Doppler and "feature tracking" methods showed the respective consistency of the results in the basal segments of myocardial ventricle walls. Conclusion Provided that echographic imaging is good, strain can be computed in athletes by both Doppler-derived and tracking methods. It is technically feasible to use both -interchangeably, at least in basal segments.